The Effect of Estradiol Administration on Muscle Mass Loss and Cachexia Progression in Female ApcMin/+ Mice - Counts, Brittany R.; Fix, Dennis K.; Hetzler, Kimbell L.; Carson, James A. (Frontiers in Endocrinology, 2019)
Abstract: Cancer cachexia is a multifactorial muscle wasting condition characterized by severe body weight and muscle mass loss which is secondary to chronic disease. The mechanistic examination of cachexia has predominately focused on the male phenotype and created significant gaps in understanding cachexia progression in the female. Female hypogonadism can accompany cancer cachexia and is characterized by reduced circulating 17ß-estradiol and uterine atrophy. Estrogen has known functions in skeletal muscle homeostasis involving the regulation of muscle protein turnover, cellular stressors, and oxidative metabolism. However, 17ß-estradiol’s ability to regulate cachexia progression in the female is not known. The purpose of this study was to determine the effect of gonadal function and estradiol administration on muscle mass loss and cachexia progression in female ApcMin/+ mice. Methods: Female C57BL/6 (B6; N=82) and ApcMin/+ (MIN; N=88) mice were used in 2 separate experiments. In experiment 1, mice were sacrificed at either 12 (N=20) or 20 (N=41) weeks of age. Body weight and estrous cycle presence was determined weekly. In experiment 2, B6 and MIN mice were randomly allocated to: Control (N=17), received E2 pellet (E2, N=18), ovariectomy surgery (OVX; N=19) or ovariectomy surgery with E2 pellet (OVX + E2; N=21). 17ß-estradiol was administered through an implanted slow-releasing pellet (0.1mg). In estrogen and ovariectomy experiments, food intake and functional outcomes were recorded one week prior to sacrifice. Results: We report that E2 administration prevented body weight loss, muscle mass loss, cage inactivity, and grip strength loss associated with cachexia. In skeletal muscle, E2 reduced skeletal muscle AMPK phosphorylation, improved mTORC1 signaling, and prevented mitochondrial dysfunction. Conclusion: Our results demonstrate a role for 17ß-estradiol for the prevention of skeletal muscle mass loss in female tumor bearing mice. Furthermore, 17ß-estradiol prevented cachexia’s disruption in skeletal muscle signaling involving AMPK and mTORC1, in addition to improving mitochondrial function in female tumor bearing mice.